2023
DOI: 10.1055/s-0043-1768035
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Survival of Patients Treated with Minimally Invasive Direct Coronary Artery Bypass (MIDCAB) Compared with the General Swiss Population

Abstract: Background To evaluate the midterm follow-up and 5-year survival outcome of the minimally invasive direct coronary artery bypass (MIDCAB) procedure compared with the survival of the general Swiss population. Methods Retrospective study on preoperative data, intraoperative data, and postoperative outcome of patients who underwent MIDCAB surgery between June 2010 and February 2019. To assess validity of this surgical therapy, outcomes were compared with survival data of a gender- and age-matched cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 27 publications
7
3
2
Order By: Relevance
“…Previously published studies reported comparable stroke and myocardial infarction (MI) rates between conventional CABG and minimally invasive approaches verifying its safety [ 15 ]. In line with previous evidence [ 8 , 10 , 16 ], our study reports no cases of perioperative stroke, no cases of new-onset dialysis, and only two cases (0.64%) of perioperative MI. In our study, we present seven cases (2.3%) of newly manifested AF, which is favorable compared to previously reported rates [ 8 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Previously published studies reported comparable stroke and myocardial infarction (MI) rates between conventional CABG and minimally invasive approaches verifying its safety [ 15 ]. In line with previous evidence [ 8 , 10 , 16 ], our study reports no cases of perioperative stroke, no cases of new-onset dialysis, and only two cases (0.64%) of perioperative MI. In our study, we present seven cases (2.3%) of newly manifested AF, which is favorable compared to previously reported rates [ 8 , 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous evidence [ 8 , 10 , 16 ], our study reports no cases of perioperative stroke, no cases of new-onset dialysis, and only two cases (0.64%) of perioperative MI. In our study, we present seven cases (2.3%) of newly manifested AF, which is favorable compared to previously reported rates [ 8 , 16 ]. We report no need for intraoperative blood transfusion in our cohort and a short duration of ICU (1.0, 0–1.0 days) and in-hospital stay (8.7 ± 5.5 days), which is comparable to previously published data [ 8 , 9 ] reporting a significantly lower proportion of transfused patients and a shorter ICU and in-hospital stay amongst MIDCAB patients [ 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…MIDCAB surgery has been proposed as a less invasive alternative to full sternotomy revascularization in isolated LAD disease or in the context of hybrid revascularization strategies. Several reports have described low perioperative morbidity and mortality and excellent long-term survival ( 15 17 ). In the largest single-center cohort of a total of 2,667 patients who underwent MIDCAB surgery over a 22-year period—the longest follow-up reported so far—Davierwala and colleagues from the Leipzig group recently reported survival estimates of 88.0, 77.7, 66.1 and 55.6% at 5, 10, 15 and 20 years, respectively, which impressively was found to be better than the age- and sex-adjusted German population.…”
Section: Discussionmentioning
confidence: 99%